Developing a Russian-Language Wisdom Diagnostics Questionnaire - Natalya N. Mekhtikhanova (Peoples' Friendship University of Russia (RUDN University), 2022)
Wisdom is an ancient concept that has acquired a new status in modern psychology. Wisdom has been proven to promote both optimal self-development and the well-being of others. However, its study requires a reliable methodological arsenal. In Russian science, work on creating methods for studying wisdom is just beginning. The subject of this study is a methodological toolkit for the empirical study of wisdom. The purpose of the study is to analyze and evaluate various methods accumulated in international psychology in recent years, as well as to create an improved version of the author's questionnaire for diagnosing wisdom. The author discuss various classifications of methods for diagnosing wisdom proposed, in particular, by such authors as R. Sternberg, W. Staudinger J. Glück, I. Grossmann. The advantages and limitations of the available methods are considered. It should be noted that quite reasonably there are a large number of self-assessment methods (questionnaires) among them. The empirical part of the work is concerned with identifying the factor structure of the original version of the author's questionnaire and its verification. The study involved 1,078 persons, including 621 women and 457 men aged 18-72. The respondents were residents of various Russian cities with higher or secondary specialized education. The IBM SPSS Statistics 18.0 and Amos 18.0 software packages were used for calculations. The conducted exploratory factor analysis revealed the four-factor structure of the developed wisdom diagnostics questionnaire (WDQ). The adequacy of the obtained model feature was proved by the confirmatory factor analysis. The empirical structure of the WDQ, formed from four correlating factors with high internal consistency, corresponds to the theoretical model, which includes four indicators: (1) cognitive sphere, (2) behavioral features, (3) humanistic orientation, and (4) spontaneity of the emotional sphere. In accordance with this model, a modified version of the WDQ has been developed. In practical terms, this will expand the possibilities of diagnosing and subsequently developing the individual's abilities to find wise solutions to critical social or interpersonal problems.